2017
DOI: 10.3945/ajcn.117.161570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium supplements on glucose metabolism in African Americans with prediabetes: a pilot trial

Abstract: Background: Low potassium has been identified both as a risk factor for type 2 diabetes and as a mediator of the racial disparity in diabetes risk. Low potassium could be a potentially modifiable risk factor, particularly for African Americans. Objective: We sought to determine the effects of potassium chloride (KCl) supplements, at a commonly prescribed dose, on measures of potassium and glucose metabolism. Design: Among African-American adults with prediabetes, we conducted a double-blinded pilot randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Since there are no studies examining the effect of sodium-potassium ratio on insulin resistance or insulin sensitivity, previous studies examined the effects of sodium or potassium on insulin resistance or insulin sensitivity, respectively. Several studies reported a positive association of high-sodium diet [ 6 7 8 9 ] or low-potassium diet [ 10 11 ] with insulin resistance that cohere with these results. Sodium intake estimated by the urinary sodium to urinary creatinine ratio was positively associated with insulin resistance among Korean children or adolescents [ 30 31 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Since there are no studies examining the effect of sodium-potassium ratio on insulin resistance or insulin sensitivity, previous studies examined the effects of sodium or potassium on insulin resistance or insulin sensitivity, respectively. Several studies reported a positive association of high-sodium diet [ 6 7 8 9 ] or low-potassium diet [ 10 11 ] with insulin resistance that cohere with these results. Sodium intake estimated by the urinary sodium to urinary creatinine ratio was positively associated with insulin resistance among Korean children or adolescents [ 30 31 ].…”
Section: Discussionsupporting
confidence: 64%
“…Wan Z et al [ 9 ] conducted a clinical trial to examine the effects of sodium and potassium on insulin resistance during 7 days, and found that a high salt diet was positively associated with insulin resistance and potassium supplements inversely associated with insulin resistance. Chatterjee R et al [ 10 ] piloted a double-blinded randomized controlled trial to compare the effects of potassium supplements (40 mEq K/d) with matching placebo during 3 months, and found a significant trend for improved insulin sensitivity among the potassium-treated group. On the other hand, no associations between sodium and insulin resistance [ 15 16 ] and negative associations between sodium and insulin resistance [ 11 12 13 14 ] were reported by several studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic status (SES) was reported by all but two studies. Participants in three studies were reported as having only a high school education or less, low-income, and/or mostly uninsured [ 20 , 54 , 55 ]. Studies were mostly conducted in large urban/metropolitan cities with only one in a rural area [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis study showed that there was a linear dose-response between low serum potassium and risk of type 2 diabetes mellitus [54]. Chatterjee et al (2017) demonstrated that potassium chloride supplementation reduced the worsening effect of fasting glucose in African-Americans compared with placebo [55]. Collectively, the evidence has shown that potassium content in durian might play a role in the regulation of blood glucose.…”
Section: Health Benefits Of Durianmentioning
confidence: 99%